Excavations at Portchester Castle Vol. V: Post Medieval 1609-1819 - Cunliffe, Barry (Reports of the Research Committee of the Society of Antiquaries of London, 1994)
In the fifth and final report on the excavations at Portchester Castle, the last stage of the castle's useful life is considered in full. The excavations undertaken between 1961 and 1979 brough to light structural evidence of the various buildings erected during the period 1609-1819, together with a large collection of varied artefacts. This evidence is presented against the backgrounds of the copious topographical and documentary record.